The Olympic Games and the Environment - Karamichas, J. author. aut Link
XII, 242 p.
Keywords: This book examines the environmental credentials of Olympic Host cities and the opportunities afforded by hosting the Games towards the ecological modernization of the host nation by using perspectives offered by environmental sociology. It also sets out projections for the environmental legacy of London 2012.